Super-tough piezoelectric material and preparation method thereof
By simultaneously salting out and stretching polymer materials in a salting-out solution, the problem of insufficient strength and toughness of fiber materials was solved, and a super-tough piezoelectric material with high strength, high toughness and high piezoelectric properties was prepared.
Patent Information
- Application Number
- CN202411683438.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Existing fiber materials are insufficient in terms of strength and toughness. Traditional glass fiber and carbon fiber have high strength but low toughness, while high-toughness fiber materials such as polyethylene nanofiber and aramid fiber have insufficient strength. Furthermore, traditional piezoelectric materials have poor flexibility or poor biocompatibility and piezoelectric properties.
By simultaneously salting out and stretching pre-formed polymer materials in a salting-out solution, combined with a shaping process, an ultra-tough piezoelectric material is prepared. Using a salting-out solution such as sodium citrate solution and a gradient cooling technique, a polymer fiber structure is formed, which enhances the toughness and piezoelectric properties of the material.
The prepared ultra-tough piezoelectric material exhibits excellent performance in terms of high strength and high toughness, with a fracture strain of nearly 60% and a piezoelectric coefficient of 20 pm/V, combining high flexibility with excellent piezoelectric properties.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material technology, and in particular to a super-tough piezoelectric material and a preparation method thereof. Background Art
[0002] Ultra-tough fibers combine the characteristics of high strength and high toughness, and have great advantages in the face of high stress and high-intensity impact loads, and can provide more reliable protection in challenging environments. Therefore, ultra-tough materials are widely used in bulletproof equipment, military applications, aerospace, medical and other fields.
[0003] Although some fiber materials are able to provide high strength and toughness, existing technologies still have some limitations. Traditional fiber materials, such as glass fiber and carbon fiber, have high strength, but their toughness is relatively low. At the same time, some high-toughness fiber materials, such as polyethylene nanofiber (UHMWPE) and aramid (Kevlar) fiber, although showing excellent toughness, their strength is sometimes not enough to meet the needs of specific applications. Therefore, a new type of material is needed to overcome the limitations of traditional fiber materials while maintaining high strength and high toughness.
[0004] Flexible electronic devices have great application potential in emerging application fields such as wearable electronic products and medical integrated devices. Piezoelectric materials are materials that can convert mechanical energy into electrical energy. Due to their unique electromechanical coupling characteristics, they are widely used in smart sensing materials. Traditional piezoelectric materials are mainly divided into two categories. One is non-polar piezoelectric ceramics, which have excellent piezoelectric properties, such as PZT (lead zirconate titanate) ceramics, strontium aluminate (SrAl2O4) ceramics, and bismuth aluminate (BiAlO3) ceramics. Although these inorganic piezoelectric ceramics have excellent piezoelectric properties, they are poor in flexibility and fragile. The other is organic piezoelectric polymers, such as PVDF (polyvinylidene fluoride) and P (VDF-TrFE) (polyvinylidene fluoride-trifluoroethylene copolymer). Although organic piezoelectric polymers have good flexibility, their biocompatibility and piezoelectric properties are poor. Therefore, the preparation of a material with both excellent piezoelectric properties and flexibility is of great significance for the development of flexible electronics. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a super-tough piezoelectric material and a preparation method thereof, so as to prepare a material having both high piezoelectric properties and high flexibility.
[0006] To achieve the above object, the present invention provides a method for preparing a super-tough piezoelectric material, comprising the following steps:
[0007] The preformed polymer material is stretched while being salted out in a salting-out solution, and after being shaped, an ultra-tough piezoelectric material is obtained.
[0008] The above-mentioned preforming is to preliminarily shape the polymer material in a salting-out solution or to preform it by freezing or drying.
[0009] The method provided by the present invention is applicable to polymer materials that can generally be shaped by salting out, freezing or drying, and the polymer materials include but are not limited to one or more of materials such as protein, polyvinyl alcohol (PVA), alginate, chitosan, hyaluronic acid, etc.; the protein preferably includes one or more of silk fibroin, gelatin, collagen, and synthetic protein. The synthetic protein may have a specific amino acid sequence according to the test requirements.
[0010] The salting-out liquid can be a solution known to those skilled in the art that can salt out and fix the polymer material, including but not limited to alcohol, ammonium sulfate, sodium citrate, sodium chloride, sodium sulfate solution, preferably sodium citrate solution. The solvent of the solution includes but is not limited to water.
[0011] The concentration of the salting-out solution is preferably 0.1 mol / L to a saturated solution, more preferably 1.5 mol / L.
[0012] The pH value of the salt solution is preferably acidic, more preferably 2-6. In some specific embodiments of the present invention, the pH value of the salt solution is 5.
[0013] The above preforming operation is to facilitate the subsequent salting-out stretching operation. The present invention has no special limitation on the temperature of the salting-out solution, and the material can be solidified to fix the shape of the core-wrapped polymer material.
[0014] Preferably, the present invention uses a solution that can provide a mold function to wrap the internal polymer solution, so that the solution that can provide a mold function is solidified and shaped, thereby pre-shaping the internal polymer solution into a fiber shape.
[0015] The present invention has no particular limitation on the specific method of curing and shaping, and a conventional curing method in the art can be selected according to the material properties.
[0016] When the encapsulating material is a gelatin material, the salting-out solution may be at a generally low temperature, including but not limited to below 10° C., or may be subjected to a gradient cooling process.
[0017] Preferably, the salting-out liquid is cooled in a gradient from 10 to 0°C. The cooling method of the gradient cooling can achieve the gradual shaping of the polymer material, making its mechanical properties more stable.
[0018] The present invention has no special limitation on the preforming time, and the preforming time is preferably 10 s to 24 h. The specific preforming time can be adjusted according to the type, temperature, pH, concentration, etc. of the salting-out solution.
[0019] In some specific embodiments of the present invention, when the salt solution is a sodium citrate solution with a pH of 5, a concentration of 1.5 M, and a temperature of -1.5°C, the preforming time is 40 minutes.
[0020] Preferably, the preforming operation steps include:
[0021] A coaxial sleeve is used, wherein the outer tube contains a solution that can provide a mold function, and the inner tube contains a polymer material solution, and the two are extruded into a salting liquid at the same time for preforming to obtain a polymer nanofiber material with a coating layer on the surface, and then the coating layer is removed;
[0022] Alternatively, a solution casting method is used to obtain a preformed polymer membrane material.
[0023] The present invention has no particular limitation on the specific type of the solution that can provide the mold function, and the solution can be a substance that has low-temperature curing and high-temperature dissolvable and removable properties well known to those skilled in the art.
[0024] Or a polymer solution that solidifies in a specific solution to obtain a shaping function, for example, an alginate solution can be shaped in a calcium ion solution, and a chitosan solution can be gelled in different pH environments.
[0025] Preferably, the solution that can provide the mold function includes but is not limited to one or more of gelatin solution, alginate solution, agar solution, hyaluronic acid solution, and chitosan solution. Gelatin solidifies at low temperatures, allowing the internal polymer solution to be pre-shaped into a fiber shape.
[0026] Preferably, the solution that can provide a mold function and the polymer solution are placed in syringes respectively, the syringe containing the solution that can provide a mold function is connected to one end of the outer tube, and the syringe containing the polymer solution is connected to one end of the inner tube, so as to inject the solution that can provide a mold function and the polymer solution into the outer tube and inner tube of the sleeve respectively.
[0027] The diameter of the outer tube is preferably 0.1-3 mm. In some specific embodiments of the present invention, the diameter of the outer tube is 1 mm.
[0028] Preferably, the outer tube has good hydrophobicity, and its material may be polytetrafluoroethylene (PTFE), polypropylene (PP), polyethylene (PE), polyurethane (PU), etc., and the hydrophilic material may also be modified, such as fluorinated coating, etc.
[0029] The diameter of the inner tube is preferably 10-500 μm. In some specific embodiments of the present invention, the diameter of the inner tube is 250 μm.
[0030] The present invention has no special limitation on the material of the inner tube, and the inner tube may be made of glass, stainless steel, polytetrafluoroethylene (PTFE), polyurethane (PU), polypropylene (PP), polyetheretherketone (PEEK) and the like.
[0031] Preferably, the orifice of the inner tube is a tapered orifice for providing shear force for extrusion.
[0032] The concentration of the solution capable of providing mold function is preferably 0.5% to 25%, more preferably 20%.
[0033] The solvent of the solution capable of providing a mold function is preferably water.
[0034] The concentration of the polymer solution is preferably 2% to 30%, more preferably 5% to 20%.
[0035] The solvent of the polymer solution is preferably one or more of water, formic acid, HFIP (hexafluoroisopropanol) and the like.
[0036] In order to ensure that the solution that can provide the mold function has good fluidity, the present invention preferably heats the outer tube so that the temperature of the solution that can provide the mold function is 30-100°C, more preferably 60-80°C.
[0037] The present invention has no particular limitation on the heating method, as long as the solution that can provide the mold function can be heated. In some specific embodiments of the present invention, a heating belt or other similar heating device is used to wrap the syringe for constant temperature heating.
[0038] The present invention controls the injection speed of the syringe to control the flow rate of the solution and the polymer solution that can provide the mold function.
[0039] Preferably, the flow rate of the solution that can provide a mold function is 2-100 ml / h, more preferably 20-70 ml / h. In some specific embodiments of the present invention, the flow rate of the solution that can provide a mold function is 30 ml / h.
[0040] Preferably, the flow rate of the polymer solution is 0.1-50 ml / h, more preferably 1-5 ml / h. In some specific embodiments of the present invention, the flow rate of the polymer solution is 1.5 ml / h.
[0041] Preferably, in the present invention, the flow rate of the solution capable of providing a mold function is 20 times the flow rate of the polymer solution, so that optimal coating can be formed.
[0042] In some specific embodiments of the present invention, the coaxial sleeve is an electrospinning coaxial needle.
[0043] The present invention has no special limitation on the shapes of the inner tube and the outer tube, which can be set according to the final shape requirements of the material, including but not limited to circular, elliptical, etc.
[0044] In some specific embodiments of the present invention, the inner tube is a heated and stretched glass tube with an inner diameter of 250 μm, and the outer tube is a PTFE tube with an inner diameter of 1 mm. The inner and outer tubes form a concentric circle structure.
[0045] Preferably, the interface between the inner tube and the outer tube is connected using a needle with a specific notch (a notch that matches the diameters of the outer tube and the inner tube) (the connection is bonded using UV glue).
[0046] In the present invention, the above-mentioned coaxial sleeve and its matching connecting needle are collectively referred to as a microfluidic chip.
[0047] The present invention uses the above device to extrude the solution that can provide mold function and the polymer solution into the salting-out liquid at the same time, so that the solution that can provide mold function and the polymer solution form a fiber structure of the polymer solution with a coating layer on the outside in the salting-out liquid.
[0048] Preferably, the salting-out liquid is cooled in a gradient of 10 to 0°C, which is a suitable temperature gradient for preforming. By gradually cooling, the solution that can provide the mold function is gradually cross-linked to become a colloid, and the internal polymer material is gradually fixed in shape, from a solution state to a solid primary fiber, thereby achieving preforming.
[0049] The present invention utilizes the characteristics of the solution that can provide mold function, which has fluidity in a high temperature environment and gelation and molding in a low temperature environment, to wrap the internal polymer material and preform the internal polymer material in a low temperature environment. After preforming, the outer coating layer is removed to obtain the preformed polymer material.
[0050] The present invention has no particular limitation on the method for removing the coating layer, and the method may be a method well known to those skilled in the art, including but not limited to removing the coating layer with hot water.
[0051] The temperature of the hot water is preferably 30-80° C., so that the coating layer melts and the internal polymer fiber material is exposed.
[0052] When preparing membrane materials, a solution casting method can be used to obtain a preformed polymer membrane material.
[0053] Preferably, the mold of the solution casting method is a pre-shaped gelatin material, and the gelatin coating layer is removed after casting to carry out subsequent salting-out, stretching and shaping.
[0054] The method for removing the gelatin coating layer is the same as above and will not be repeated here.
[0055] Alternatively, the polymer solution is cast in other molds, frozen preformed or dried preformed, and then taken out from the mold.
[0056] The present invention can obtain film materials of different shapes by adjusting the shape of the mold.
[0057] The temperature of the hot water is preferably 30-80° C., so that the gelatin melts and the internal polymer fiber material is exposed.
[0058] Then, the preformed polymer material is stretched while being salted out in the salting-out liquid.
[0059] The present invention has no special limitation on the stretching method. The two ends of the polymer material can be fixed to achieve stretching while salting out in the salting out liquid; or a collecting roller can be used to achieve stretching by differential traction during the collection process.
[0060] The stretching speed of the stretching is preferably 0.1-500 mm / min; more preferably 1-50 mm / min. In some specific embodiments of the present invention, the stretching speed is 1 mm / min.
[0061] The stretching ratio is preferably 0.1 to 10 times, more preferably 1 to 3 times.
[0062] The stretching salting-out liquid can be a solution known to those skilled in the art that can salt out and fix the polymer material, including but not limited to alcohol, ammonium sulfate, sodium citrate, sodium chloride, sodium sulfate solution, preferably sodium citrate solution. The solvent of the solution is preferably water.
[0063] The concentration of the salting-out solution is preferably 0.1 mol / L to a saturated solution, and more preferably 1.5 mol / L.
[0064] After stretching, the material is shaped. Preferably, the stretched material is placed in a salting-out liquid for static salting-out, and then the salt on the surface and inside of the material is removed.
[0065] The temperature of the salting-out solution is preferably -10 to 35°C, more preferably 0 to 5°C.
[0066] The static salting-out time is preferably 0 to 24 hours.
[0067] The salting-out solution for setting can be a solution that can salt out and set the polymer material, which is well known to those skilled in the art, including but not limited to alcohol, ammonium sulfate, sodium citrate, sodium chloride, sodium sulfate solution, etc., preferably sodium citrate solution. The solvent of the solution is preferably water.
[0068] The concentration of the salting-out solution is preferably 0.1 mol / L to a saturated solution, and more preferably 1.5 mol / L.
[0069] Through the above method, the toughness and fracture strain properties of fiber materials, such as silk fibroin materials, can be greatly improved.
[0070] The present invention also provides a super-tough piezoelectric material prepared by the above preparation method.
[0071] The test results show that the fracture strain and toughness of the material prepared by the present invention are greatly improved. The fracture strain can reach nearly 60%, the toughness is close to that of spider silk, and the piezoelectric coefficient can reach 20pm / V. At the same time, higher toughness and piezoelectric properties are obtained.
[0072] Compared with the prior art, the present invention provides a method for preparing a super-tough piezoelectric material, comprising the following steps: salting out and stretching a preformed polymer material in a salting-out solution, and obtaining a super-tough piezoelectric material after shaping. The present invention changes the secondary structure of the protein inside the fiber through the synergistic effect of preforming and salting out while stretching, thereby improving the toughness and piezoelectric properties of the fiber material, and preparing a piezoelectric material with both high piezoelectric properties and high flexibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 It is a schematic diagram and a partial enlarged diagram of the microfluidic device;
[0074] Figure 2 is a schematic diagram of the preformed fiber structure;
[0075] Figure 3 This is a photo of the SF fiber that has been preformed and the gelatin has been removed;
[0076] Figure 4 The actual pictures of SF fibers before salting-out stretching (top) and after salting-out stretching (bottom);
[0077] Figure 5 It is the 1 times tensile stress-strain curve;
[0078] Figure 6 It is a 2 times tensile stress-strain curve;
[0079] Figure 7 It is a 3 times tensile stress-strain curve;
[0080] Figure 8 This is the AFM piezoelectric performance test image of a single fiber;
[0081] Fig. 9 This is the SEM morphology of the SF fiber surface prepared in Example 1;
[0082] Fig.10 This is the FTIR characterization graph of the SF fiber prepared in Example 1 stretched 2 times;
[0083] Fig.11 This is the FTIR characterization graph of the SF fiber prepared in Example 1 stretched 1 times;
[0084] Fig.12 This is the FTIR characterization graph of the SF fiber prepared in Example 1 stretched 3 times;
[0085] Fig.13 It is a summary diagram of the secondary structure content of different fiber stretching multiples;
[0086] Fig.14 This is a tensile stress-strain curve of the SF fiber prepared in Example 2;
[0087] Fig.15 This is the AFM piezoelectric performance test image of the SF fiber prepared in Example 2;
[0088] Fig.16 This is a comparison diagram of the mechanical properties of the membrane before and after stretching and salting out in Example 3;
[0089] Fig.17 These are sample pictures of the membrane before and after stretching and salting out in Example 3. DETAILED DESCRIPTION
[0090] To further illustrate the present invention, the super-tough piezoelectric material and its preparation method provided by the present invention are described in detail below in conjunction with the embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.
[0091] All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods well known to those skilled in the art.
[0092] Example 1
[0093] 1. Preforming
[0094] Prepare two syringes: inject 20% gelatin and 20% silk fibroin (SF) solution respectively. Wrap the gelatin syringe with a constant temperature heating tape and heat it at 80°C to maintain good fluidity of gelatin;
[0095] Microfluidic chip: This device is mainly composed of two coaxial circular tubes, which are composed of heated and stretched glass tubes (inner diameter 250μm) and PTFE tubes (inner diameter 1mm). The two tubes form a concentric circle structure. The interface of the two tubes is connected by a needle with a specific notch (the notch that matches the diameter of the outer tube and the inner tube) (the connection is bonded with UV glue). The heated and stretched glass tube is used as the inner tube to extrude the silk protein solution at a flow rate of 1.5ml / h, and the PTFE tube is used as the outer tube to extrude the gelatin solution at a flow rate of 30ml / h. The inner tube and the needle are connected to the syringe using a transparent hose with an inner diameter of 0.7mm.
[0096] Figure 1 The schematic diagram and partial enlarged diagram of the microfluidic device are shown in Figure 1. Figure 2 Schematic diagram of preformed fiber.
[0097] The microfluidic chip was extruded into a gradient cooling device with a temperature gradient of 10~0℃ from top to bottom.
[0098] After the fiber was extruded, it was placed in a 1.5 M sodium citrate solution for salting out for 40 min to preform the internal SF solution. The gelatin was then removed in hot water at 60 °C.
[0099] 2. Salting and stretching
[0100] The stretching device is improved from a stepper motor and equipped with two 7cm metal rods to meet the requirements of stretching in a salting solution. During stretching, pure SF, from which gelatin is removed by hot water, is glued to two metal rods of the stretching machine with UV glue for stretching at a speed of 1mm / min and a stretching multiple of 3. The salting solution is a 1.5M sodium citrate solution.
[0101] Figure 3 This is a photo of the pre-formed product with the gelatin removed.
[0102] Figure 4 These are the actual pictures before salting out stretching (top) and after salting out stretching (bottom).
[0103] 3. Material fixation
[0104] After stretching, the material was placed in a salting solution (1.5 M sodium citrate) for subsequent stable salting for 24 hours. After salting, the material was soaked in deionized water to remove the salt on the surface and inside of the material, and an ultra-tough piezoelectric fiber material was obtained.
[0105] The prepared fiber material is stretched 1 to 3 times, and the stress-strain curve of the stretched fiber is as follows: Figures 5 to 7 As shown, the tensile test shows that the fracture strain and toughness of the SF fiber prepared by the present invention are greatly improved, and the fracture strain can reach nearly 60%.
[0106] Tensile tests were performed on native degummed silk fibers and regenerated silk fibers reported in the literature, and the results showed that their breaking strains in the dry state were both around 20%.
[0107] The piezoelectric properties of the single fiber prepared by the present invention were tested using the PFM mode of AFM, and the piezoelectric coefficient can reach 20 pm / V. Figure 8 shown.
[0108] The piezoelectric properties of silk fibroin that has not been treated with salting-out and stretching were tested, and its piezoelectric coefficient was 0.36 pm / V.
[0109] The morphology of the fiber material prepared in this application is detected, such as Fig. 9 As shown, the upper and lower figures are SEM morphology images at different magnifications. It can be seen that the prepared fiber has a smooth surface and a diameter of about 20 μm.
[0110] The secondary structures of SF fibers with different stretching ratios were characterized by FTIR. Figure 10-13 It is found that the content of β-folding, which has a greater influence on the fiber properties (mechanical and piezoelectric), first increases and then decreases with the increase of the stretching ratio, reaching a maximum value when the stretching ratio is 2.
[0111] Example 2
[0112] The preparation method is the same as that in Example 1, without changing other conditions. When the concentration of the salting-out solution during salting-out and stretching is 0.5 M, the breaking strain of the prepared SF-3 fiber can be increased to 62%.
[0113] Fiber mechanical properties Fig.14 , piezoelectric properties see Fig.15 .
[0114] Example 3
[0115] The preparation method is the same as that of Example 1, except that the preforming is performed by freezing, and then the salting-out treatment is performed while stretching.
[0116] Specifically, a silk fibroin (RSF) solution (concentration 20%) was poured into a PDMS mold (length 40 mm, width 5 mm, height 3 mm) with a rectangular groove, and placed in a -80°C refrigerator for freezing. Then, the sample was demolded and placed in a salting-out solution (1.5 M sodium citrate solution) for 4 hours to preform the membrane material. Subsequently, the stretching was performed while salting out at a stretching multiple of 1. The other conditions were the same as the fiber stretching in Example 1 to prepare a stretched membrane.
[0117] Comparison of membrane mechanical properties before and after stretching and salting out Fig.16 As shown, the experimental results show that the fracture stress and fracture strain of the membrane are greatly improved by salting out while stretching.
[0118] Fig.17 The following are sample images of the membrane before and after stretching and salting out. The left image is a preformed sample that has not been stretched, and the right image is a sample that has been stretched while salting out. Fig.17 It can be seen that the color of the sample changes from transparent to opaque after stretching, which may be caused by the increase in its degree of crystallinity.
[0119] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a super-tough piezoelectric material, comprising the following steps: The preformed polymer material is stretched while being salted out in a salting-out solution, and after being shaped, an ultra-tough piezoelectric material is obtained.
2. The preparation method according to claim 1, characterized in that: The preforming is preforming of the polymer material in a salting-out solution, or is frozen preforming or dried preforming.
3. The preparation method according to claim 1, characterized in that: The preforming operation steps include: A coaxial sleeve is used, wherein the outer tube contains a solution that can provide a mold function, and the inner tube contains a polymer material solution, and the two are extruded into a salting liquid at the same time for preforming to obtain a polymer nanofiber material with a coating layer on the surface, and then the coating layer is removed; Alternatively, a solution casting method is used to obtain a preformed polymer membrane material.
4. The preparation method according to claim 3, characterized in that: The solution that can provide mold function is selected from one or more of gelatin solution, alginate solution, agar solution, hyaluronic acid solution, and chitosan solution; The diameter of the outer tube is 0.1-3 mm; the diameter of the inner tube is 10-500 μm; The flow rate of the solution that can provide mold function is 2-100 ml / h; The concentration of the solution that can provide mold function is 0.5% to 25%; Heating the outer tube so that the temperature of the solution capable of providing the mold function is 30-100° C.; The flow rate of the polymer solution is 0.1-50 ml / h; The concentration of the polymer solution is 2% to 30%; The mold of the solution casting method is a pre-shaped gelatin material, and the gelatin coating layer is removed after casting, or other molds are used to cast the polymer solution, and then frozen or dried for pre-forming, and then taken out from the mold.
5. The preparation method according to claim 1, characterized in that: The stretching is: fixing the two ends of the polymer material and stretching it in a salting liquid; or using a collecting roller and completing the stretching by differential traction during the collection process; The stretching speed of the stretching is 0.1 to 500 mm / min; The stretching ratio is 0.1 to 10 times.
6. The preparation method according to claim 1, characterized in that: The stereotype is: The stretched material is placed in a salting-out liquid for static salting-out, and then the salt on the surface and inside of the material is removed.
7. The preparation method according to claim 6, characterized in that: The temperature of the salting-out solution is -10 to 35°C; The static salting-out time is 0 to 24 hours.
8. The preparation method according to any one of claims 1 to 7, characterized in that The salting-out liquid is selected from a solution of alcohol, ammonium sulfate, sodium citrate, sodium chloride, and sodium sulfate; The concentration of the salting-out solution is 0.1 mol / L ~ saturated solution.
9. The preparation method according to any one of claims 1 to 7, characterized in that: The polymer material is selected from one or more of protein, polyvinyl alcohol, alginate, chitosan, and hyaluronic acid; The protein includes one or more of silk fibroin, gelatin, collagen, and synthetic protein.
10. The super-tough piezoelectric material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of secondary structure controllable silk fibroin porous material with no need of organic solvent
CN105749343A
Flexible transparent piezoelectric composite film, transparent stretchable ultrasonic transducer and preparation method thereof
CN113801412A
High-toughness nano composite fiber and preparation method thereof
CN117926445A
Electro-Mechanically Stretched Micro Fibers and Methods of Use Thereof
US20150118195A1
Cited By
Silk fibroin piezoelectric material and preparation method thereof
CN120350440A
A silk fibroin piezoelectric material and its preparation method
CN120350440B